Explicit Vocabulary Instruction with English Language Learners: a Charade Game - Mala Khayati; Muhamad Sofian Hadi (English Language in Focus (ELIF), 2020)
The present study aimed to determine the efficacy of students' vocabulary mastery by Charade Game. This research has used 8th students of SMPN 18 KOTA TANGERANG SELATAN as a sample population. There had been 30 students throughout this group. The researchers used a simple cluster sampling technique to select the sample. The method of this study was quantitative and a quasi-experimental design of the pre-test and post-test. The data used for this study were gathered through pre-test and post-test vocabulary. Pre-test and post-test data then were analyzed numerically via SPSS19. The findings of this research clarified that the student pre-test score was 57 but then after treatment, the student post-test score was 81.83. The findings also indicate that the tobtained value was 15.79 and the tcritical value was 0.05. These findings mean that Charade Game was likely to succeed in mastering vocabulary.